KONDISI PERAIRAN TERHADAP STRUKTUR KOMUNITAS MAKROZOOBENTHOS DI MUARA SUNGAI KARANGANYAR DAN TAPAK, KECAMATAN TUGU, SEMARANG - Retno Astrini, Ananda Dhea; Yusuf, Muh; Santoso, Adi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The estuary water of Karanganyar and Tapak Rivers receives wastes originated from landbased activities mainly factories discharging to both rivers. The wastes entering to the estuary may result the pollution and, in turn, affecting the water and organisms that live in it including the physical-chemical quality of the water and macrozoobenthic community. The aims of the research were to study the physical-chemical conditions of the water and to study the macrozoobenthos in relation to the contaminants. The method in this study was a case study with the samplings done three times at intervals of 2 weeks. The results of the study and analysis indicated that some chemical properties of the water were above the upper the limits required by the Sea Water Quality Standard. The chemical properties are DO, BOD â‚…, nitrate, phosphate and ammonia. The IMLP were analysis showed that the water was in the middle criteria. The analysis results of the macrozoobenthic diversity index showed that the water was polluted in heavy level. Based on the study there were 15 genera of macrozoobenthic identified in the study area. The entire genera were divided into 4 classes, gastropods (3 genera), Bivalves (4 genera), Polychaets (7 genera) and crustaceans (1 genus). Factors affecting differences in the degree of similarity at each station observed was the difference in water quality conditions thought to be the dominant influence of the mass of river water or the sea water, so the variation of environmental parameters among stations were relatively the same. Substrate texture of the bottom of each station was generally in the form of mud (silt).